Indonesian Presidential Election 2019 – Abangan, Santri, and Priyayi : Three Streams in Indonesia’s Electoral Politics - Syafiq Hasyim (2019)
The categorisation of abangan, santri and priyayi remains relevant for discussion in the Indonesian general election of 2019. These groups exist and political parties and presidential candidates compete vigorously for their votes.